Peran Masyarakat Lokal Dalam Upaya Pencapaian Tujuan Pembangunan Berkelanjutan (SDGS) : Studi Kasus Subak Jatiluwih - Suseno, Imadul Umah; Saputra, Beny Mahyudi (Gorontalo State University, 2025)
This research examines the challenges faced in achieving the Sustainable Development Goals (SDGs) in Jatiluwih Village, which include land conversion, the impact of tourism development, and farmer regeneration. The method used is a qualitative approach through in-depth interviews, focus group discussions, and field observations, involving local communities as research subjects. The purpose of this study is to explore the active role of the community in the preservation of the Subak system and its contribution to the achievement of SDGs, especially SDGs 1, 8, and 15. The results of the study show that community participation in the management of Subak is very important to maintain agricultural sustainability, improve economic welfare, and preserve the ecosystem. Thus, a participatory approach has proven to be the key in overcoming various challenges and ensuring the sustainability of the Subak system in Jatiluwih